STUDENT'S PERCEPTION TOWARDS THE USE OF EDMODO IN LEARNING EFFECTIVE LISTENING IN THE PANDEMIC COVID-19 PERIOD - Gratiana Sama; Maria Kristina Ota; Gregoriana Apriliani Siam (Universitas Muhammadiyah Makassar, 2021)
Virtual class or commonly referred to as online class is one form of learning media that uses the Internet specifically during the quarantine of covid-19. Quantitative descriptive analysis in this study examines the student’s perception of English Literature Study Program Universitas Flores about the use of the Edmodo platform in Effective Listening class at the time of Covid-19 quarantine. The number of samples in this study is 44 students of English Literature Study Program of Universitas Flores who have been taken Effective Listening class during the Covid-19 quarantine period. The result is that Edmodo platform used in Effective Listening class was positive. The average of 98% of English Literature Study Program Students of Flores University agreed to use Edmodo applications as learning media to learn Effective Listening Class at Covid-19 quarantine time since it is user-friendly. This is because Edmodo's interface looks like a Facebook as social media that students have known in their daily lives